The determinants of skills use and work pressure: A longitudinal analysis. (August 2019) - Felstead, Alan; Gallie, Duncan; Green, Francis; Henseke, Golo
Employers, workers and governments all have a stake in improving intrinsic job quality since it can help to raise worker well-being and lower the social costs of ill-health. This article provides a unique insight into factors triggering changes to two key aspects of intrinsic job quality – the skills used and developed at work, and the pressures under which work is carried out. Using a rare two-wave panel dataset, the article assesses whether three predicted determinants – namely employee involvement, teamworking and computerisation – are good or bad for these aspects of intrinsic job quality.